A Study Correlation Between Hand Pain And Practicing Duration In Pistol Shooting Sports - Gavali, Mrunmai Nitin; Sagar, Javid H (Journal of Neonatal Surgery, 2025)
Background: Pistol shooting is a precision sport that requires sustained grip strength and motor control. Long hours of training may lead to musculoskeletal discomfort, particularly in the hand and forearm. This study aims to assess the correlation between hand pain and years of practice in pistol shooters, using the Cornell Hand Discomfort Questionnaire and Numeric Pain Rating Scale. Methods: A cross-sectional observational study was conducted with 97 pistol shooters from Kolhapur. Participants were categorized based on their practice duration: 1-3 years (Beginner), 3-6 years (Intermediate), and more than 6 years (Advanced). Data collection involved demographic details, practice history, and pain assessment using validated tools. Statistical analysis was performed to determine the relationship between practice duration and hand discomfort. Results: The study revealed that 82.47% of shooters reported experiencing hand pain, with pain intensity being higher during movement (Mean = 3.19) than at rest (Mean = 1.96). The mean Cornell Hand Discomfort Questionnaire score was 37.14 (SD = 21.85), indicating varied discomfort levels. Advanced shooters (>6 years of practice) reported the highest pain levels. Despite uniform training durations (2 hours daily), prolonged practice years were significantly associated with increased discomfort. Conclusion: The findings suggest there is no correlation between hand pain and practicing duration in pistol shooters.